Dynamics of scientific production on Acrididae (Orthoptera) in Brazil: A bibliometric analysis of themes and impact (Research, Society and Development, 2025)
This study presents a bibliometric analysis of scientific production on grasshoppers of the Acrididae family in Brazil, aiming to identify patterns of publication, academic impact, collaboration networks, and thematic structure. Data were collected from the Web of Science and Scopus databases, covering the period from 1979 to 2025. The analysis was conducted using R software, with the Bibliometrix and Biblioshiny packages. Thematic maps reveal a predominance of basic taxonomic and ecological studies, with emerging niches in molecular genetics and aquatic ecology. The keyword co-occurrence network highlights thematic fragmentation in the field, with two major clusters: one focused on taxonomy and biogeography, and another on the ecology of wet environments. The conceptual structure map and dendrogram reinforce this division, pointing to the need for greater interdisciplinary integration. It is concluded that research on Acrididae in Brazil has solid foundations but requires thematic renewal, methodological diversification, and expansion of international collaborations.